DRAMA AS A KIND OF LITERATURE AND A FORM OF ART: CURRENT ISSUES OF ITS STUDY AT SCHOOL - Khorob, Stepan (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The main purpose of the article is to propose for study (in secondary and higher schools) topical issues of the theory and history of drama as a kind of literature and art form. Attention is paid to the kinship and difference of drama with other types of literature – epics and lyrics; on its features of functioning and characteristic features of – action, drama, conflict, character, stage; on methods of analysis of a dramatic work. Therefore, the study has a novelty, connected primarily with the consideration of analytical judgments about drama in its theoretical and historical-literary, as well as theatrical aspects, aimed at an in-depth understanding of its nature and specificity. The methodological basis in the study of the problem is the following methods: philological, cultural-historical and hermeneutic. This also includes theoretical foundations in literary studies and theater studies. Research results: the need to know the peculiarities of drama as a kind of literature and a form of art in educational activities for educational and pedagogical workers, as well as the educational process for pupils and students, has been proven. The practical significance of the article is that its main provisions and conclusions can be used during the study of the works and work of playwrights in secondary and higher schools, in research on drama and theater.